Análisis de la defectología en probetas de acero soldadas, utilizando inspección visual y el método de tintas penetrantes en los procesos smaw y gmaw con variación de sus parámetros principales - Avilés Miño, Marcos Alberto (2017)
This research project was conducted in order to analyse the defectology in steel welded specimens, using visual inspection (VT) and dye penetrant test (PT) in SMAW and GMAW with variation of the main parameters, so as to identify the defects that occur when a change occurs in its main parameters and thus to be able to know the cause and effect that this leads, this is undoubtedly a very important information either in a didactic way for the students or for the companies dedicated to the metal mechanic industry from the city. To accomplish this analysis firstly we made the WPS (Welding Procedure Specification) according to AWS D1.1 standard for SMAW and GMAW process respectively. The weld of ASTM A36 steel specimens was done taking into account the previously performed WPS, designing with the number 1 the specimen of each process (both SMAW and GMAW) that complied with the prescribed WPS, the others (designed with successive numbers) suffered changes in the parameters of welding, so that the analysis and comparison of the results can be performed. In total, 14 specimens were made, 8 for GMAW process and 6 for SMAW process. The visual inspection (VT) consisted of the evaluation of each specimen, analysis of defects found in both the face and the root of the weld and data collect for the report of each respectively, these data were verified after the realization of the test using dye penetrant where they could be evidenced the defects already found with the visual inspection and also other defects not perceptible to the eye. This led to a report on the main defects in welding processes, SMAW and GMAW, when a change in its main parameters was made, based on the specifications of the welding procedure recommended for each process. This research tries to improve the quality of welding processes by reporting through the report the defects that can occur with the change of non-recommended variable or bad practice of the welder in the SMAW and GMAW processes in a way that contributes to the optimization of the quality in the welding, something of which in the city exists deficiency. Keywords: Welding, steel, defects, inspection, non-destructive testing